2010
DOI: 10.2174/156720510793611628
|View full text |Cite
|
Sign up to set email alerts
|

Tau Pathology and Future Therapeutics

Abstract: The current review discusses microtubules and tau in the healthy brain and move on to the underling pathology of Alzheimer's disease (AD) with emphasis on tau and neurofibrillary tangles. Tangles have been associated with cognitive dysfunction causing neurodegeneration in the absence of plaques. AD, the most abundant tauopathy is characterized by β-amyloid plaques and tau tangles. An abundance of tau inclusions, in the absence of β-amyloid deposits, defines Pick's disease (frontotemporal lobar degeneration), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 151 publications
(193 reference statements)
1
22
0
Order By: Relevance
“…The link was supported by pathological findings including the interaction between α-synuclein and tau, and the presence of tau in the Lewy bodies of typical PD (Lei et al, 2010;Arima et al, 1999). Furthermore, tau mutations cause atypical PD syndromes, such as progressive supranuclear palsy, and corticobasal degeneration (Gozes, 2010). While the hyperphosphorylation of tau causes toxicity (Morris et al, 2011), increasing evidence also supports a possible role for functional loss of tau protein in both diseases, as soluble tau is reduced in the affected regions in both disorders (Lei et al, 2012;Kosik et al, 1989;Zhukareva et al, 2001).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The link was supported by pathological findings including the interaction between α-synuclein and tau, and the presence of tau in the Lewy bodies of typical PD (Lei et al, 2010;Arima et al, 1999). Furthermore, tau mutations cause atypical PD syndromes, such as progressive supranuclear palsy, and corticobasal degeneration (Gozes, 2010). While the hyperphosphorylation of tau causes toxicity (Morris et al, 2011), increasing evidence also supports a possible role for functional loss of tau protein in both diseases, as soluble tau is reduced in the affected regions in both disorders (Lei et al, 2012;Kosik et al, 1989;Zhukareva et al, 2001).…”
Section: Introductionmentioning
confidence: 88%
“…Tau protein is extensively implicated in the pathogenesis of AD and considered as a potential drug target (Gozes, 2010). Recent genomewide association studies identified a significant association between the MAPT locus and sporadic PD (Lei et al, 2010;Nalls et al, 2014), indicating a possible pathological link between tau and PD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show tau as a potential diagnostic marker and a candidate for change and maintenance via drug application. [53][54][55] In this work, we propose the future design of Alzheimer's therapy in that the tangle protein and molecular motor can be trapped, transported, and received into the optical waveguide by optical tweezers. By utilizing the reasonable optical pulse input power, the dynamic tweezers can be controlled and stored within the system before reaching the final destination via the molecular buffer and bus network.…”
Section: Resultsmentioning
confidence: 99%
“…This selective review on VIP-PACAP-ADNP-NAP that highlights the current issue of the Journal of Molecular Neuroscience paves the path to new and original research. Our additional comprehensive reviews are accessible for perspective reading (Gozes 2007(Gozes , 2008Gozes 2010;Gozes et al 2005;Gozes et al 2009). New and exciting findings will be presented at the forthcoming VIP-PACAP and related peptides meeting in Eilat, Israel, 2011.…”
Section: Editorial: From the Desk Of The Editor-in-chiefmentioning
confidence: 99%